Examining the Impact of Critical Thinking on Beninese EFL Beginners’ Classes - TEBA, Corneille Sourou (My University, 2019)
This research work tackles the impact of critical thinking on EFL beginners’ classes. The aim of this study is to show the advantages learners could benefit from the effective teaching of critical thinking in beginners’ classes. The methodology adopted during the investigation consists in collecting information from EFL teachers and learners through the means of classroom observation and questionnaires. The data obtained from questionnaires have been analyzed and discussed in order to draw out relevant conclusions. The results found show that learners are unaware of the impact of critical thinking and teachers do not sacrifice most of their time to teach this skill. EFL Teachers should reconsider this skill and search for ways to implement it.
Keywords: Critical thinking; impact; classes; results; advantages